In Vitro Study of Magnetic Resonance Imaging Artifacts of Anesthetic Devices - Bajracharya, Uday; Rawal, Prabhat (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Deep sedation or general anesthesia is usually required for Magnetic Resonance Imaging when patients cannot remain motionless in the suite. Various anesthetic devices have been used to maintain the airway and ventilate the lungs during this period but some of them produce artifacts that pose difficulties in the interpretation of images. The aim of this study was to identify the devices that produced artifacts during Magnetic Resonance Imaging. Methods: Twelve anesthetic devices were considered: oro-pharyngeal airway, naso-pharygeal airway, face mask with reservoir bag, nasal cannula, endotracheal tube, disposable Ambu Laryngeal Mask Airway, Laryngeal Mask Airway Unique, Disposable Laryngeal Tube Sonda, i-gel, Ambubag, Bain Circuit, Jackson Rees Circuit.Magnetic Resonance Imaging was performed with each device placed on the top of a phantom simulator respectively to resemble the position in vivo. Results: The artifacts with Disposable Laryngeal Tube Sonda, Laryngeal Mask Airway Unique and endotracheal tube were related to ferromagnetic material in the pilot valve were similar. No artifacts were found with oro-pharyngeal airway, naso-pharygeal airway, nasal cannula, endo-tracheal tube with pilot valve detached, face masks with reservoir bag (metal removed), Ambu bag (without Adjustable Pressure Limiting valve), i-gel , disposable Ambu Laryngeal Mask Airway, Bain Circuit and Jackson Rees Circuit. Conclusions: Anesthetic devices not containing any ferromagnetic material are recommended for use during MRI scanning to reduce artifacts.